203k views
2 votes
-5(3-2x)-(1-x)=4(x-3)

User JosephC
by
5.3k points

1 Answer

4 votes

Answer:

x = 4/7 = 0.571

Step by step solution :

Step 1 :

Equation at the end of step 1 :

((0-(5•(3-2x)))-(1-x))-4•(x-3) = 0

Step 2 :

Equation at the end of step 2 :

((0-5•(3-2x))-(1-x))-4•(x-3) = 0

Step 3 :

Equation at the end of step 3 :

7x - 4 = 0

Step 4 :

Solving a Single Variable Equation :

4.1 Solve : 7x-4 = 0

Add 4 to both sides of the equation :

7x = 4

Divide both sides of the equation by 7:

x = 4/7 = 0.571

PLEASE SAID THANKS

User Tejeshree
by
6.1k points